Financial Development Influence on Economic Growth in Albania - Musta, Eugen (European Journal of Economics and Business Studies, 2016)
During the 2000s the private banking sector in Albania started to consolidate and the level of lending in the economy started to grow. In the same period the overall economic indicators were showing positive growth too, but that all changed after the financial crisis of 2008. It took a while for its effects to hit the country but when they came the economy started to slowdown and the banks while facing a rise in Non-Performing Loans (NPL) started to cut out lending. The drop on lending is considered a problem by policy makers who see a pattern of causality in the finance – growth nexus based on theoretical works saying that finance development can influence growth. Even though the theory linking economic growth with financial development is not unanimously accepted on academic circles, empirical studies support the fact that a better developed financial system helps to support a sustainable growth. This seems enough to keep policy makers concerned with keeping lending high in the economy. The purpose of this study is to find if there is a pattern of such correlation between lending and growth in the Albanian economy. For the purpose data from the last 21 years have been analyzed through a time series regression where per capita GDP growth rate is the dependable variable and the domestic credit to private sector by banks is undependable variable. For the analyze is based on the aggregate demand model where credit is influencing investments, the influence which government spending may have on output is tested it the regression as an influential factor. The result showed that the explanatory variable coefficient is negative, suggesting that in this case the financial sector growth has a negative effect on growth. We assume this is so because the main channel through which the finance influences growth, which is by allocating capitals towards the most efficient opportunities, is not actually working and this can be seen by the high number of non-performing loans on the banks’ balance sheets.
Keywords: Lending, GDP growth, Albania, finance-growth nexus, financial development